Improving project delivery process using lean construction approach - Adamu, Samaila (2017)
The poor image of the Nigerian construction industry arising from suboptimal performance in project delivery due to colossal wastes is well documented in existing literature. However, effort to proffer solutions to the problems of waste on site has been marginal. After an in-depth literature review it was established that, lean construction approach has been adopted to address waste and non-value adding activities and improved productivity in project delivery. Therefore, this study is aimed at proposing a lean implementation framework (LIF) that will guide the site implementation of lean construction tools to address the waste occurrence menace. Accordingly, action research using mixed-mode approach was adopted, data related to waste occurrences and benefits of lean construction was collected. This was conducted in two phases. The first phase sought to explore the frequency and level of waste and non-value adding activities occurrences in project delivery in Nigerian construction sites. To achieve this aim, data was collected using survey questionnaire administered to 400 experts in construction industry, and tested for internal reliability using Cronbach Alpha. Consequently, the data was analysed using descriptive and inferential statistics and validated using one sample t-test. The results showed the existence of wastes that leads to cost and time overrun. The second phase assessed six lean construction tools via six case study sites. Data was collected through observation, interview, questionnaire and site diary, and analysed thematically using content analysis. The results were validated using methodological triangulation. The results showed that the application of lean construction techniques in Nigerian construction sites could address the problems of waste and non-value adding activities and improve productivity. The study identifies several challenges and barriers that could impede the implementation of lean construction, including lack of knowledge on lean approach, cultural issues, misconception by participants, and lack of involvement of designers in the implementation process. In view of these findings, the study recognises training, enlightenment on benefits of lean, involvement of designers in the implementation process, simplifying the process, trust between the project participants and collaborative planning as strategies for addressing the problems. To facilitate implementation of the suggested solutions to waste occurrences, a lean implementation framework (LIF) was developed to guide the site implementation of lean construction for improving the project delivery process. The LIF was validated using expert opinions by face to face interview, and the result revealed that the framework could be a guide for implementation of lean in construction site.